2019
DOI: 10.1021/acsami.9b12531
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Supramolecular Polyoxometalate Hybrid Architecture as a Multifunctional Oxidation Catalyst

Abstract: Polyoxometalates (POMs) are widely applied as tuneable and versatile catalysts for a variety of oxidation reactions in an aqueous/organic twophase system. However, the practical applications of POMs-based biphasic catalysis are hampered by low space-time yields and mass-transport limitation between two layers due to extremely low solubility of the organic reactants in the aqueous phase. Here, we first introduced β-cyclodextrin (β-CD) as an inverse phase transfer agent and a supramolecular nanoreactor to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 80 publications
0
33
1
Order By: Relevance
“…The chaotropic character of Keggin POMs has been clearly demonstrated, while some of them have even been identified as superchaotrope entities according to the Hofmeister classification. ,, Indeed, it has recently been shown that the strength of such supramolecular host–guest associations depends mainly on the charge density of the POM. , Furthermore, ITC measurements revealed that processes driven by the chaotropic effect exhibit specific thermodynamic signatures corresponding to enthalpy gain correlated to entropic penalty . Some of these hybrid CD/Keggin composites have shown improved performances in catalysis or adsorption, for which cooperative effects should play a crucial role. Therefore, a deeper characterization of the interactions between γ-CD and mixed-metal Keggin POMs is needed for a better understanding of the synergetic effect between the two components and further innovative development of advanced composite materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chaotropic character of Keggin POMs has been clearly demonstrated, while some of them have even been identified as superchaotrope entities according to the Hofmeister classification. ,, Indeed, it has recently been shown that the strength of such supramolecular host–guest associations depends mainly on the charge density of the POM. , Furthermore, ITC measurements revealed that processes driven by the chaotropic effect exhibit specific thermodynamic signatures corresponding to enthalpy gain correlated to entropic penalty . Some of these hybrid CD/Keggin composites have shown improved performances in catalysis or adsorption, for which cooperative effects should play a crucial role. Therefore, a deeper characterization of the interactions between γ-CD and mixed-metal Keggin POMs is needed for a better understanding of the synergetic effect between the two components and further innovative development of advanced composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, ITC measurements revealed that processes driven by the chaotropic effect exhibit specific thermodynamic signatures corresponding to enthalpy gain correlated to entropic penalty. 11 Some of these hybrid CD/ Keggin composites have shown improved performances in catalysis 18 or adsorption, 19 for which cooperative effects should play a crucial role. Therefore, a deeper characterization of the interactions between γ-CD and mixed-metal Keggin POMs is needed for a better understanding of the synergetic effect between the two components and further innovative development of advanced composite materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[2] Among the commercially available organic building units, cyclodextrins (CDs) as natural amphiphilic macrocyclic polysaccharides are particularly useful to develop host-guest systems with POMs, offering the possibility to design self-healing, stimuli-responsive, catalytic or energy-related systems. [3][4][5][6][7][8][9] The inclusion complexes involving CDs and POMs can be roughly divided in two families. In one hand, hybrid POMs with grafted organic ligands can exhibit high affinity towards hydrophobic hosting cavity.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely thanks to the complementarity of their molecular structures and is driven predominantly by favourable steric-fitting between the host and the guest oxocluster, and some hydrogen-bonding interactions. 21,86,184 Such inclusion complexes are stable in both solution and the solid-state and have recently been studied for their phase-transfer catalytic properties, 185 and as a novel tool for probing the self-assembly behaviours of small POMs by mass spectrometry. 186,187 That said, the formation of stable host-guest complexes between conventional POMs and cavitands (particularly curcubiturils and pillar-arenes, which do not share the excellent complementarity found in POMCCD systems) remains the exception rather than the rule, and in many cases, POM@cavitand complexes form crystalline networks in which the POM remains external to the macrocyclic cavity and often requires additional functionalisation of the macrocycle (e.g.…”
Section: Hybrid Pom Complexes With Cavitandsmentioning
confidence: 99%